Evaluation of the California Mastitis Test to determine udder health status of early lactation dairy cows - R.T. Dingwell; K.E. Leslie; J.M. Sargeant; Y.H. Schukken (Kansas Agricultural Experiment Station Research Reports, 2002)
Quarter milk bacteriology results of samples collected within the first week of calving were used to calculate the test characteristics of the California Mastitis Test (CMT) that estimate the udder health status of fresh dairy cows. Over 1,200 quarters were both cultured and had a CMT performed. The overall sensitivity and specificity of the CMT was 68.8% and 71.5%, respectively. Using a cutpoint of any CMT reaction as a positive test and examining the results by various days in milk, the highest sensitivity and specificity occurred at day four (82.4% and 80.6%, respectively). The CMT has the potential to be a useful tool for monitoring udder health in fresh cows.; Dairy Day, 2002, Kansas State University, Manhattan, KS, 2002;
Keywords: Dairy Day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-121-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 898; Dairy; CMT; Udder health; Fresh cow